2017
DOI: 10.1016/j.molmet.2017.10.005
|View full text |Cite
|
Sign up to set email alerts
|

AMPK activation caused by reduced liver lactate metabolism protects against hepatic steatosis in MCT1 haploinsufficient mice

Abstract: ObjectiveHepatic steatosis is the first step leading to non-alcoholic fatty liver disease, which represents a major complication of obesity. Here, we show that MCT1 haploinsufficient mice resist to hepatic steatosis development when fed a high fat diet. They exhibit a reduced hepatic capacity to metabolize monocarboxylates such as lactate compared to wildtype mice.MethodsTo understand how this resistance to steatosis develops, we used HFD fed wildtype mice with hepatic steatosis and MCT1 haploinsufficient mice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
28
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 30 publications
3
28
0
Order By: Relevance
“…injection), control of glycemia at 0, 15, 30, 45, 60, and 120 min after injection. [47,48] Alanine and glutamine tolerance tests Glutamine and alanine are two major amino acids transported from the muscles during periods of active gluconeogenesis. Therefore.…”
Section: Discussionmentioning
confidence: 99%
“…injection), control of glycemia at 0, 15, 30, 45, 60, and 120 min after injection. [47,48] Alanine and glutamine tolerance tests Glutamine and alanine are two major amino acids transported from the muscles during periods of active gluconeogenesis. Therefore.…”
Section: Discussionmentioning
confidence: 99%
“…Its activation in the liver favors energy producing and not energy consuming processes such as fatty acid synthesis (Carneiro et al. ). This downregulation of energy consuming processes is achieved through the inhibition of the sterol regulatory element binding protein 1 (SREBP1) and consequently repressing key transcription factors such as peroxisome proliferator‐activated receptors (PPAR) that are involved in lipid metabolism (Carneiro et al.…”
Section: Introductionmentioning
confidence: 99%
“…This downregulation of energy consuming processes is achieved through the inhibition of the sterol regulatory element binding protein 1 (SREBP1) and consequently repressing key transcription factors such as peroxisome proliferator‐activated receptors (PPAR) that are involved in lipid metabolism (Carneiro et al. ). It is important, however, to note that while the upregulation of AMPK protects against hepatic steatosis, its downregulation does not indicate susceptibility to hepatic steatosis (Boudaba et al.…”
Section: Introductionmentioning
confidence: 99%
“…Adenosine monophosphate‐activated protein kinase (AMPK) is a crucial cellular energy sensor that is activated by changes in physiological conditions mediated by metabolic hormones, different cell stress conditions, and also pharmacological molecules (Carling, ; Hardie, Schaffer, & Brunet, ). Once activated, AMPK promotes changes in energy levels (Hardie, Ross, & Hawley, ; Qiu et al, ), or a shift in glucose metabolism toward lactate metabolism in tumors and MCT1+/− mice (Carneiro et al, ; Faubert et al, ; Lage, Dieguez, Vidal‐Puig, & Lopez, ). Furthermore, our recent study suggested that AMPK acts as a negative regulator of hyperthermia‐induced lactate secretion by decreasing the expression levels of GLUT3 , LDHA , and MCT1 in cultured boar SCs (Yu et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…physiological conditions mediated by metabolic hormones, different cell stress conditions, and also pharmacological molecules (Carling, 2017;Hardie, Schaffer, & Brunet, 2016). Once activated, AMPK promotes changes in energy levels (Hardie, Ross, & Hawley, 2012;Qiu et al, 2018), or a shift in glucose metabolism toward lactate metabolism in tumors and MCT1+/− mice (Carneiro et al, 2017;Faubert et al, 2013;Lage, Dieguez, Vidal-Puig, & Lopez, 2008).…”
mentioning
confidence: 99%